Adherence strength of T cells to planar membranes containing LFA-3 molecules - Tozeren, A; Sung, K; Sung, L; Dustin, M; Chen, P; Springer, T; Chien, S (1991)
Cell adhesion plays a fundamental role in cell motility and immune response. We investigated the adhesion between a Jurkat cell, chosen for its high expression of CD2, and a glass-supported planar membrane containing either the laterally mobile, lipid-anchored isoform (GPI LFA-3) or the immobile, transmembrane isoform (TM LFA-3) of the counter-receptor LFA-3 at the same concentration of 2,000 LFA-3 molecules/μm2 by using a novel micromanipulation method. In this technique, the pipette holding the cell is micromanipulated in the direction perpendicular to a glass-supported lipid bilayer reconstituted with a given type of surface adhesion molecules. In experiments using the planar membrane containing GPI LFA-3, the adhered Jurkat cell deformed extensively in response to the pipette force, as the cell detachment proceeded by peeling at the edges of the contact area. When the cell elongation in the direction of the pipette reached a maximum, the cell separated rapidly from the planar membrane. In experiments using the planar membrane containing TM LFA-3, Jurkat cells detached with little resistance to micromanipulation and without changing their round shape. Our experimental data showed that the aspiration pressure required to detach a Jurkat cell from a membrane containing mobile LFA-3 is about one order of magnitude greater than that for the immobile LFA-3.